Simple Maths

  • Thread starter frozen7
  • Start date
  • #1
164
0
((-6)^ 1/2 ) ( (-7)^1/2) = (42)^1/2

((-6)^ 1/2 ) ( (-7)^1/2) = (6^ 1/2 ) ( 7^1/2) ( i ^2)
= -(42)^1/2

Can anyone tell me where I did wrong?
 

Answers and Replies

  • #2
lurflurf
Homework Helper
2,432
132
frozen7 said:
((-6)^ 1/2 ) ( (-7)^1/2) = (42)^1/2

((-6)^ 1/2 ) ( (-7)^1/2) = (6^ 1/2 ) ( 7^1/2) ( i ^2)
= -(42)^1/2

Can anyone tell me where I did wrong?
((-6)^ 1/2 ) ( (-7)^1/2) = (42)^1/2
this step
[tex]x^zy^z=(xy)^z[/tex]
is not true in general only when x,y>0
 
  • #3
((-6)(-7))^(1/2)=(42)^(1/2)
(42)^(1/2)=(42)^(1/2)
should have left the right hand side alone
 
  • #4
164
0
Thanks a lot..
 

Related Threads on Simple Maths

  • Last Post
Replies
5
Views
1K
  • Last Post
Replies
17
Views
2K
  • Last Post
Replies
2
Views
2K
  • Last Post
Replies
18
Views
2K
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
8
Views
1K
  • Last Post
Replies
10
Views
2K
  • Last Post
Replies
1
Views
1K
  • Last Post
Replies
5
Views
1K
  • Last Post
Replies
5
Views
807
Top